Informational Asymmetry in Public Participation on Environmental Monitoring in Indonesian Regulation: A Preliminary Discourse - Daniel, Deni; Hapsari, Palupi (UI Scholars Hub, 2019)
Public participation has been viewed as crucial component in environmental management. Public participation enables the community to inform the project proponents and government agencies on local knowledge and aspiration to be considered in decision-making process. Based on our literature review we found that effective participation in monitoring might be hampered by informational asymmetry and the opportunistic nature of firms. In the case of Indonesia, little has been discussed on the possible informational asymmetry on the public participation process in environmental management. This paper aims to give a normative analysis on the current regulation of public participation in Indonesia to identify possible informational asymmetry that might give barrier to effective monitoring. Our discussion found that there are still gaps in access to relevant information in the current mechanism of public participation. This is due to a prematurely informational disclosure and the lack of projects and decisions follow-up towards community by both firms and government agencies. This set a barrier for the community to obtain credence information which comprised of the firms’ environmental requirements and obligations and the highly technical aspects of environmental monitoring. We suggest a proper way to address this obstacle by reforming public participation regulation.